Perubahan elektroensefalografi pada demensia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Dementia is a syndrome that consists of a decline in cognitive and intellectual abilities occuring in an awake and alert patient, which is severe enough to interfere significantly with work, regular social activities, or relationships with others. Electroencephalography (EEG) may be useful in the evaluation of dementia. It can aid in the differentiation of a degenerative disorders, such us Alzheimer's disease, with pseudo-dementia due to psychiatric illness. Furthermore, EEG changes in dementia are usually related to severity of illness. Thus EEG can be normal, particularly early in the course of the illness when the diagnosis is clinically more difficult.